Medication Literacy Among Consumers at Community Pharmacies in Hanoi and Vinh Phuc - Thi Bich Thao, Cao; khanh Long, Dang; Thi Thu, Bui; Trung Kien, Nguyen; Thi Thuy Van, Pham (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 41 No 4, 2025)
Abstract: Objective: To assess medication literacy and identify related factors among consumers at community pharmacies. Subjects and methods: A cross-sectional descriptive study was conducted by interviewing consumers at 5 community pharmacies in Hanoi and Vinh Phuc regarding their medication literacy (using the ChMLM tool) and related characteristics, from October 2024 to January 2025. Results: A total of 742 individuals participated in the interviews. Among the participants, 55.7% were male, with a mean age of 54.1 years, and 32.2% were aged 65 years or older. A total of 63.7% reported having chronic diseases, while 49.5% indicated regular use of medication. Approximately 59.4% stated that they always or often read medication instructions. Notably, 48.1% of the participants demonstrated low levels of medication literacy. Factors associated with lower medication literacy included being over 65 years old, living in Vinh Phuc, having an acute illness, and infrequent reading of medication instructions. Conversely, higher education was associated with a higher literacy level. Conclusion: Medication literacy among participants at community pharmacies remains limited, influenced by factors such as age, education level, residential area, health status, and reading habits. More effective educational and counseling interventions are needed to improve the community’s medication literacy. Keywords: Medication literacy, drug consumers, community pharmacy, associated factors.